Nurses' perception on the reception and classification of risk in Primary Health Care - Costa, Ariane Beatriz (2018)
This study emerged as a proposal for change in the work process in health services that pay attention to the population, especially spontaneous demand. The objective was to know the perception of nurses about the reception and classification of risk in primary health care. It is a descriptive study with a qualitative approach. Sixteen nurses interviewed participated. The analysis of the data resulted in three categories: Knowledge and responsibilities of the reception, applicability of the classification of risks and protocols, and difficulties in the reception. The results showed that the concept of reception and classification of risk are recognized by the nurses, but in the applicability of both processes they find difficulties in the responsibility of the reception and in the ignorance of the users in relation to the forms of attention. It is concluded that although the importance of reception and its resolution is recognized, the need to train and create addressing protocols is confirmed.